EVALUASI PENGELOLAAN DANA DESA PADA KECAMATAN BANGUNREJO KABUPATEN LAMPUNG TENGAH - Muhammad Bhakti Syuhodo; Bambang Suhada; Muhammad Ihsan Dacholfany (Universitas Muhammadiyah Metro, 2021)
This study aims to determine and test empirically: 1) Management of village funds management in Tanjung Jaya Village, Bangunrejo District, Central Lampung Regency. 2). Factors that become obstacles to the management of village funds in Tanjung Jaya Village, Bangunrejo District, Central Lampung Regency. 3). Supporting factors in managing the allocation of village funds in Tanjung Jaya Village, Bangunrejo District, Central Lampung Regency. This research was conducted in Tanjung Jaya Jaya Village, Bangunrejo District, Central Lampung Regency. This research is a qualitative descriptive study. The results showed that the management of village funds carried out by the Village Government of Tanjung Jaya and Sri Pendowo had followed the technical guidelines set out in statutory regulations. In the process, the two villages have been optimal in 2018 and 2019, while in 2020 the village of Tanjung Jaya is not optimal, while the village of Sri Pendowo has been optimal. This can be seen from the budget that does not match the realization. The implementation of Village Fund management in Tanjung Jaya Village is less effective and efficient and uneven and insufficient, in 2020. This is because the objectives that have been formulated by the Village Fund Allocation policy have not been fully achieved. The management of Sri Pendowo village funds has been effective, efficient, equitable and sufficient from 2018-2020. Supporting factors for village management are community participation in program planning and program implementation, such as participating in road development mutual cooperation and others. Lack of community supervision in the implementation of management, limited resources and lack of control over information systems (operating computers), causing weaknesses in the preparation of SPJ